Pengklasifikasian Penerimaan Beasiswa Bidikmisi FMIPA UNP Tahun 2016 dengan Menggunakan Metode Classification and Regression Trees - Elfin Innaka Hamidah; Yenni Kurniawati (Journal of Mathematics UNP, 2018)
Abstract – This study discussed about classification of Bidikmisi Scholarship Recipient. The classification was used by Classification and Regression Trees (CART) to college students who proposed Bidikmisi in Mathematics and Natural Sciences Faculty of State University of Padang at 2016. The purpose of this research is to determine characteristic of college student recipient and not recipient of Bidikmisi Scholarship based on seven variable that influence. Optimally Trees was obtained with choose the best separator based on maximal improvement values. Optimally trees was produced four variable, father’s occupation, mother’s occupation, Father’s Income, and building area. Characteristic of college student who bidikmisi recipient was parent’s occupation as farmer or etc. (as like as unemployment, the taxi bike, construction laborers, etc.) and father’s income  one million. While characteristic of college student that not bidikmisi recipient were Father’s occupation as civil servants, employees, entrepreneurship, or fisherman.